METAPHOR IN WESTLIFE SONGS LYRIC OF SPECTRUM ALBUM - Zalogo, Ricca Albertin (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2022)
This researcher aimed to analyze the metaphor in Westlife songs lyric of Spectrum album. This researcher was designed by using qualitative research. While, the data of this research is metaphor in Westlife songs lyric of Spectrum album. The data collected were analyzed by using Miles, Huberman, and saldana (2014), namely data condensation, data display, and drawing/verifying conclusion. The result of data analysis showed that there are 4 types of metaphor in the Spectrum album. They are 14 active metaphor, 11 asymmetric metaphor, 2 subjective metaphor, and 5 mimetic metaphor. The 4 types of metaphor found in Westlife songs are talking about love, life, and family. Based on the research finding, it is concluded that from the 6 types of metaphor, only 4 types that are found in Spectrum album and dominant types are active metaphor. So, it is suggested to use the song as media to find the figurative language, especially metaphor.